2009
DOI: 10.1152/ajpheart.01041.2008
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II disproportionally attenuates dynamic vagal and sympathetic heart rate controls

Abstract: To better understand the pathophysiological role of angiotensin II (ANG II) in the dynamic autonomic regulation of heart rate (HR), we examined the effects of intravenous administration of ANG II (10 microg.kg(-1).h(-1)) on the transfer function from vagal or sympathetic nerve stimulation to HR in anesthetized rabbits with sinoaortic denervation and vagotomy. In the vagal stimulation group (n = 7), we stimulated the right vagal nerve for 10 min using binary white noise (0-10 Hz). The transfer function from vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
4
12
1
Order By: Relevance
“…Nevertheless, the sympathetic transfer function approximated a second‐order delay system (Fig. 2) and its parameters were similar to those estimated between postganglionic sympathetic stimulation and HR response in rabbits (natural frequency, 0.06–0.07 Hz; damping coefficient, 1.34–1.53; and lag time, 0.51–0.65 s; Kawada et al 2009). If we calculate the corner frequency (frequency at which gain decreased by 3 dB from steady‐state gain; 0.04 ± 0.01 Hz) instead of natural frequency, our results are comparable to the corner frequency (0.01–0.02 Hz) found by Berger et al .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the sympathetic transfer function approximated a second‐order delay system (Fig. 2) and its parameters were similar to those estimated between postganglionic sympathetic stimulation and HR response in rabbits (natural frequency, 0.06–0.07 Hz; damping coefficient, 1.34–1.53; and lag time, 0.51–0.65 s; Kawada et al 2009). If we calculate the corner frequency (frequency at which gain decreased by 3 dB from steady‐state gain; 0.04 ± 0.01 Hz) instead of natural frequency, our results are comparable to the corner frequency (0.01–0.02 Hz) found by Berger et al .…”
Section: Discussionsupporting
confidence: 61%
“…As preliminary results suggested that the transfer function from sympathetic stimulation to HR response in rats approximated a second‐order low‐pass filter with pure delay, as in the case of rabbits (Kawada et al 1996, 2009), we determined the parameters of the sympathetic transfer function using the following equation: where K is dynamic gain (in beats per minute per herz), f N is the natural frequency (in herz), ζ is the damping ratio, L is lag time (in seconds), and f and j represent frequency and imaginary units, respectively. The dynamic gain ( K , in beats per minute per herz) represents the asymptotic value of transfer gain as the frequency approaches zero, and corresponds to the steady‐state response in the step response.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, Ang-II pressor responses were associated with a fall in vagal discharge (three fibers), little change (4 fibers) or an increase, but an increase smaller than occurred in response to PE (1 fiber). In a recent and elegant study in anesthetized rabbits with SAD and vagotomy, Kawada, et al (2009) stimulated the peripheral end of the right vagus with vs. without background iv Ang-II administration (10 ng/kg/min). They reported that the gain of the transfer function from vagal stimulation to HR slowing decreased significantly with concomitant Ang-II administration vs. control (i.e., no Ang-II).…”
Section: Discussionmentioning
confidence: 99%
“…) and reduces the dynamic gain of the transfer function from VNS to HR (Kawada et al . ). Du et al .…”
Section: Discussionmentioning
confidence: 97%